Clean Development Mechanism (CDM) after the first commitment period: Assessment of the world׳s portfolio and the role of Latin America. (January 2015) - Watts, David; Albornoz, Constanza; Watson, Andrea
Abstract: The clean Development Mechanism (CDM) represents the main effort to help developing countries develop sustainably and developed countries to reach their emission reductions targets set under the Kyoto Protocol. With the ending of the first commitment period, there is an opportunity to assess the state of the CDM portfolio (2008–2012). This article is the first effort to evaluate the CDM portfolio throughout the first commitment period, as well as the first paper focused on Latin America׳s CDM portfolio as a whole, concentrating on renewable energy projects. Moreover, a special analysis is performed for Chile, Latin America׳s third most important CDM country (after Brazil and Mexico), 6th worldwide (after China, India, Korea, Brazil and Mexico) and first in CERs registered among the small countries, an ideal host because of its high political stability, government effectiveness, access to capital and regulatory quality. In addition, a study was performed on 180 renewable energy projects in Latin America, revealing that the additionality assessments performed under the CDM are too subjective, hindering the validation of the projects and their transparency. The main policy implication of this research is to expose the need for a radical change to the succeeding document to the Kyoto Protocol in order to reduce the inequality amongst host countries and ensure that CDM fulfills its sustainable development claim. Some of the proposed measures include establishing uniform benchmarks to be used against similar projects, a thorough validation for declared barriers, simplifying the registering process, and providing international aid for the least developed countries that have historically lacked the ability to participate in the CDM.